Rural Industrialisation in India: the changing profile - Rao, R.V. (Delhi, 1978)
India is a land of villages and eighty per cent of our population live in rural areas. The rural sector is contributing more than 50 per cent to our national income. However, in spite of many years of planning, we have not been able to ensure a minimum standard of living to the teeming millions. Forty per cent of the urban population and 50 per cent of the rural population in India are still below the poverty line. The poverty of the rural population is due to population explosion, low farm productivity, unemployment, underemployment and stagnation in operational structure. The increasing population on one hand and the limited employment absorption capacities in agriculture on the other force us to go in for industrialisation in a big way as an alternative source of income, employment and expansion. Western capital intensive technology adopted by us has only given rise to islands of prosperity in a vast ocean of poverty and misery. There is thus need for increasing reliance on small industries to raise the standard of living of the rural masses, employ the human resources and prevent distress migration to urban areas. The need for rural industrialisation was also stressed by the Father of the Nation, Mahatma Gandhi. An attempt has been made in the volume to deal with the fundamental issues connected with rural industrialisation, steps taken so far and the need for taking appropriate steps to provide necessary infrastructural facilities for the same. A new edition of this useful publication, prescribed as a text book, is being issued to meet the popular demand